131k views
2 votes
Pls solve this question step by step solution.​

Pls solve this question step by step solution.​-example-1

1 Answer

3 votes

Answer:

42, 12)

Explanation:

Let the present ages of the father and son be x years and y years respectively.

According to the question,

Condition I,

Three years ago the sum of the ages of the father and his son was 48 years.

or,(x−3)+(y−3)=48

or,x−3+y−3=48

or,x−6=48−y

or,x=54−y - (i)

Condition II,

Three years hence the father's age will be three times the son's age,

or,(x+3)=3(y+3)

or,x+3=3y+9 - (ii)

Put value of x from equation (i) in equation (ii), we get,

or,(54−y)+3=3y+9

or,54−y=3y+9−3

or,54−6=3y+y

or,48=4y

or,y=484

∴y=12

Put the value of y in equation (i), we get,

or,x=54−12

∴x=42

So, (x,y) = (42, 12)

Therefore, the required present ages of the father and the son are 42 years and 12 years respectively.

User ELKA
by
7.2k points